2011
DOI: 10.1074/mcp.r111.008565
|View full text |Cite
|
Sign up to set email alerts
|

Building and Searching Tandem Mass Spectral Libraries for Peptide Identification

Abstract: Spectral library searching is an emerging approach in peptide identifications from tandem mass spectra, a critical step in proteomic data analysis. Conceptually, the premise of this approach is that the tandem MS fragmentation pattern of a peptide under some fixed conditions is a reproducible fingerprint of that peptide, such that unknown spectra acquired under the same conditions can be identified by spectral matching. In actual practice, a spectral library is first meticulously compiled from a large collecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
45
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(51 citation statements)
references
References 54 publications
0
45
0
2
Order By: Relevance
“…Some tools take advantages of known spectra and use spectral library databases. 50 Many software packages are well-established for these purposes: examples include Sequest, 51 Mascot, 52 X!Tandem, 53 pfind, 54 Skyline, 55 Sonar, 56 ProbID, 57 Popitam, 58 and Andromeda. 59 For complete lists of software tools, please refer to the following recent reviews.…”
Section: Mass Spectrometry and Its Applications To Identify Histonmentioning
confidence: 99%
See 1 more Smart Citation
“…Some tools take advantages of known spectra and use spectral library databases. 50 Many software packages are well-established for these purposes: examples include Sequest, 51 Mascot, 52 X!Tandem, 53 pfind, 54 Skyline, 55 Sonar, 56 ProbID, 57 Popitam, 58 and Andromeda. 59 For complete lists of software tools, please refer to the following recent reviews.…”
Section: Mass Spectrometry and Its Applications To Identify Histonmentioning
confidence: 99%
“…59 For complete lists of software tools, please refer to the following recent reviews. 4850,60 Mascot and Sequest are the most widely used commercial search engines. Popular protein sequences database, for example, Uniprot, NCBInr, and International Protein Index (IPI), can be used to construct mass fingerprints database.…”
Section: Mass Spectrometry and Its Applications To Identify Histonmentioning
confidence: 99%
“…Spectral library (25) search is an emerging approach to peptide identification that relies on an archive of identified tandem mass spectra. Comparing spectra to previously identified spectra is faster, more sensitive, and more accurate than comparing spectra to a sequence database.…”
Section: Resultsmentioning
confidence: 99%
“…The former are used to derive relatively unsophisticated in silico theoretical fragmentation spectra (Cottrell 1994;Eng et al 1994;Yates et al 1995;Geer et al 2004;Fenyo and Beavis 2003), while the latter contain previously identified experimental MS/MS spectra (Lam 2011)(NIST: http://peptide.nist.gov) and have been shown to outperform sequence database searching under optimal conditions . One can also generate a realistic spectral library from a sequence database using detailed MS/MS spectrum prediction (Zhang 2004(Zhang , 2005Yen et al 2011;Yen et al 2009), but this is a more complicated process.…”
Section: From Acquired Data To Processed Resultsmentioning
confidence: 99%